2017
DOI: 10.1007/978-3-319-66610-5_27
|View full text |Cite
|
Sign up to set email alerts
|

Targeting At-risk Students Using Engagement and Effort Predictors in an Introductory Computer Programming Course

Abstract: Abstract. This paper presents a new approach to automatically detecting lower-performing or "at-risk" students on computer programming modules in an undergraduate University degree course. Using historical data from previous student cohorts we built a predictive model using logged interactions between students and online resources, as well as students' progress in programming laboratory work. Predictions were calculated each week during a 12-week semester. Course lecturers received student lists ranked by thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…This allowed researchers and Faculty to gather a fine-grained digital footprint of students learning programming at our University [5]. Recently, research in Learning Analytics has focused on Predictive Modelling and identifying those students having difficulties with course material, also in programming courses [9], and offering remediation, personalized feedback and interventions to students using Machine Learning techniques [6,8]. Prior work has reported that customized notifications sent to students regarding their performance and offering resources such as further learning material, code solutions from peers in their class and university support services helped students to increase their differential performance and engagement on these programming courses [7].…”
Section: Datamentioning
confidence: 99%
“…This allowed researchers and Faculty to gather a fine-grained digital footprint of students learning programming at our University [5]. Recently, research in Learning Analytics has focused on Predictive Modelling and identifying those students having difficulties with course material, also in programming courses [9], and offering remediation, personalized feedback and interventions to students using Machine Learning techniques [6,8]. Prior work has reported that customized notifications sent to students regarding their performance and offering resources such as further learning material, code solutions from peers in their class and university support services helped students to increase their differential performance and engagement on these programming courses [7].…”
Section: Datamentioning
confidence: 99%
“…However, after identifying those "at-risk" students, we should intervene and help those students. Targeting these weak students during laboratory sessions can aid some students [2], but lecturers usually do not have the time or resources to support many students in large classes or to spend as much time identifying what the student knows and does not know. Automatic interventions for programming classes are having great success in other institutions and environments and we are eager to develop our own strategies using our platforms and resources.…”
Section: Related Workmentioning
confidence: 99%
“…Laboratory sessions and computer-based examinations are carried out during the teaching period. Our previous study [2] was done on Computer Programming I, CS1, that introduces firstyear students to computer programming and the fundamentals of computational problem solving during their first semester. We work with the following courses that are taught in the second semester (Fall): , that was taught to second-year EC students for the first time on the first semester.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations